An exploratory study to understand water, sanitation, and hygiene practices and their perceived impact on health status amongst women of reproductive age residing in an urban slum of New Delhi, India - Khan, Sumaira; Kumar, Vishal; Gawde, Nilesh; Dash, Antaryami (International Journal Of Community Medicine And Public Health, 2022)
Background: Disadvantaged urban slums in India are prone to water, sanitation, and hygiene (WASH) inadequacies. Due to biological necessities and sociocultural context of India, women remain one of the most vulnerable groups prone to the negative consequences of WASH inadequacies. This study explored the WASH practices among women residing closer to the community-managed toilet (CMT) in the slum locality of South-West Delhi to determine critical linkages to WASH inadequacies that can be used to improve accessibility, usage, and care provided by the CMT. Objectives of the study were to understand the WASH practices and the perceived physical and psychosocial impact on women residing closer to the CMT. Methods: Qualitative study using thematic content analysis. Free-list interviews and FGD were conducted to collect data to explore the perceived health effects of WASH practices among the women of the community. Results: We found that WASH practices are defined by concerns across multiple dimensions and can lead to adoption of harmful coping strategies. An interplay of sociocultural, infrastructural and household and community level factors acts as mediating factors to limit the usage of WASH facilities which may seemingly look available and accessible to women in disadvantaged urban locations. Conclusions: Access to improved WASH facilities does not imply usage and women are disproportionately burdened by WASH inadequacy. Practices such as reduced eating at night to avoid open defecation and fear of violence threaten women’s physical and psychosocial health and well-being. Priority public health attention should be given to the linkages between women’s health and inadequate WASH practices.